Valoración del efecto de un gel cicatrizante a base de Eucalipto (Eucalyptus Globulus Labill) en el tratamiento de heridas en Cobayos (Cavia porcellus) - Jaramillo Chang, Andrea Jacqueline (2023)
The present work is carried out in the Faculty of Agricultural Sciences of the Technical University of Babahoyo, where the healing effect of the Gel obtained from the extract of Eucalyptus globulus labill is evaluated in the control of wounds in Cavia porcellus, for the elaboration of the gel it is 800 g of Eucalyptus globulus labill + 800 mL of 90% ethanol were used, with a maceration time of 15 days. To this extract, 10 g of triethanolania + 10 g of carbopol + 800 ml of water were added for the final preparation of the healing gel, 24 animals are used in the study, the wounds of 12 of them were treated with healing gel while the rest were not treated. The evolution of the gel wounds was evaluated through controls and measurements of the inflamed area and closed wound, as well as the change in skin color and adverse reactions that topical use can cause until final recovery. The guinea pigs treated with the healing gel completely closed their wounds at 8 days and their scab fell in average time was 21 days, while the guinea pigs that were not treated with the gel closed their wounds at 12 days and the time of scab fall was at 28 days. Eucalyptus globulos labill extract gel is a very economical natural product with easy access to make, very useful in the treatment and regeneration of wound tissue and skin.